Molecular characterisation of carbapenem-resistant Enterobacter cloacae complex in Colombia: blaKPC and the ‘changing landscape’ - De La Cadena, Elsa; Correa, Adriana; Muñoz, Juan Sebastián; Rojas, Laura J.; Hernández-Gómez, Cristhian; Pallares, Christian; Perez, Federico; Bonomo, Robert A.; Villegas, Maria V. (Journal of Global Antimicrobial Resistance, 2018)
•Enterobacter cloacae complex (Ecl) is an important antibiotic-resistant nosocomial pathogen.•Emergence of carbapenem-resistant Ecl harbouring carbapenemases is a serious clinical threat.•Co-resistance to other classes of antibiotics leaves the clinician without therapeutic options.•Molecular epidemiology suggests potentially epidemic lineages associated with spread of β-lactamases. The aim of this study was to examine the population structure of representative carbapenem-resistant Enterobacter cloacae complex (CR-Ecl) isolates from eight different Colombian regions and to characterise their associated β-lactamases. A total of 28 CR-Ecl isolates collected in Colombia between 2009–2013 through the Colombian Nosocomial Network were included in this study. Antimicrobial susceptibility testing was performed by the broth microdilution method. Molecular detection of carbapenemase and extended-spectrum β-lactamase (ESBL) genes and the presence of transposon Tn4401 was evaluated by PCR and DNA sequencing. Genetic relatedness was assessed by multilocus sequencing typing (MLST) and repetitive sequence-based PCR (rep-PCR). PCR and DNA sequencing revealed that 19/28 (68%) of the CR-Ecl isolates carried blaKPC-2. Analysis of the genetic environment found blaKPC-2 within transposon Tn4401b in 8/19 isolates (42%). Population genetic analysis using rep-PCR revealed four clonal groups. MLST showed a variety of sequence types (STs), among which ST510 was the most common (10/28 isolates; 36%). blaKPC-2 was discovered as the most common mechanism of carbapenem resistance in CR-Ecl and was disseminated among different STs. Although none of the previously reported major clonal complexes were identified, it appears that local strain lineages are associated with the spread of blaKPC within CR-Ecl in various regions of Colombia.